Peningkatan Kemampuan Sosial-Emosional Siswa Kelompok B melalui Media Buku Cerita Kenabian: Studi Tindakan Kelas pada Raudlatul Athfal Muslimat 10 Manyar Gresik - Nina Nuriyah Ma’arif; Maskanah (Atthiflah: Journal of Early Childhood Islamic Education, 2020)
This article discusses how to improve social-emotional abilities of early childhood through the medium of the storybooks about the prophets in Raudlatul Athfal Muslimat (RAM) 10 Manyar Gresik. This study used classroom action research (CAR). The techniques of data collection and analysis were carried out through a mixed-methods approach, namely quantitative and qualitative descriptive. In this regard, the data collection technique used observation, interviews, documents, and questionnaires. While the data analysis technique utilised descriptive statistics and qualitative analysis procedures such as categorising and interpreting the data found the ground, subsequently making conclusions. The study found that through the medium of the storybooks of the prophets' stories, the social-emotional ability of group B students have developed, namely in the first cycle, it increased to 76%, ie 7 children developed suited to expectations and 6 children very well-developed . Whereas, in the second cycle, students’ emotional social abilities increased to 86%; 3 children developed suited to expectations and 10 children very well-developed.